Pengaruh Corporate Social Responsibility, Ukuran Perusahaan, Profitabilitas, Leverage dan Capital Intensity Terhadap Agresivitas Pajak - Dewi Riani Silvani; Warsito Kawedar (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2025)
This study aims to analyze the effect of Corporate Social Responsibility, firm size, profitability, leverage, and capital intensity on tax aggressiveness in mining sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021– 2023 period. This research is motivated by the prevalence of tax aggressiveness practices in the mining sector, which have the potential to reduce state revenue, making it important to identify internal company factors that influence such practices. The study employs a quantitative approach with a population consisting of all mining companies listed on the IDX, from which 84 companies were selected as the sample using a purposive sampling method based on predetermined criteria. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 26. The results show that CSR, profitability, and leverage have no significant effect on tax aggressiveness. In contrast, firm size has a positive and significant effect, indicating that larger companies tend to have higher levels of tax aggressiveness. Meanwhile, capital intensity has a negative and significant effect, meaning that a higher proportion of fixed assets is associated with lower tax aggressiveness. These findings indicate that company scale and asset composition are important factors influencing tax strategies in the mining sector. The results are expected to serve as valuable considerations for various stakeholders, including companies, policymakers, academics, and the public, in understanding and monitoring taxation practices to ensure they are conducted ethically and in compliance with regulations.